2022
DOI: 10.1186/s12877-022-02954-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between platelet, white blood cell count, platelet to white blood cell ratio and sarcopenia in community-dwelling older adults: focus on Bushehr Elderly Health (BEH) program

Abstract: Background Sarcopenia is a progressive age-related skeletal muscle disorder associated with harmful impacts on health. The present study aimed to investigate the relation between sarcopenia, platelet (PLT), white blood cell (WBC), and PLT to WBC ratio (PWR) due to the importance of early sarcopenia diagnosis. Methods This cross-sectional study was conducted based on the second stage of the Bushehr Elderly Health (BEH) Program. Sarcopenia was define… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…The results of the current study showed that there was a significant Increment when compared non-hemodialysis patients with hemodialysis patients According to the table indicated. That's agreement with previous studies [17]. Blood lead levels were significantly correlated with the red blood cell count, haemoglobin, and hemocrit measurements [14].…”
Section: Parameter Of Bloodsupporting
confidence: 93%
“…The results of the current study showed that there was a significant Increment when compared non-hemodialysis patients with hemodialysis patients According to the table indicated. That's agreement with previous studies [17]. Blood lead levels were significantly correlated with the red blood cell count, haemoglobin, and hemocrit measurements [14].…”
Section: Parameter Of Bloodsupporting
confidence: 93%
“…The effect of platelet and WBC counts can be simultaneously assessed by the PWR ( 54 ). The interaction between platelets and WBCs has been implicated in the pathogenesis of numerous diseases ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets affect other blood cells by releasing chemokines and membrane ligands and facilitating leukocyte-platelet aggregates in the peripheral blood ( 56 ). Consequently, PWR can reflect the degree of inflammation, and a significant association of PWR with diabetes may indicate a more prominent effect of PLTs than WBCs ( 54 ). During inflammation, the proportion of larger platelets tends to rise, likely due to the production of factors that encourage coagulation and inflammation, as well as the release of platelets stored in the spleen ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Medical examination was done by physicians, and then registered in a le assigned to each of people accompanying the data from their laboratory test (12).…”
Section: Medical Examinationmentioning
confidence: 99%